Probe into Stock-market Efficiency in Nepal - Sthapit, Arhan (PYC Nepal Journal of Management, 2010)
Efficient Market Hypothesis: Few Empirical Evidences from Nepalese Stock Market; By Jeetendra Dangol; Published By: Quest Publication, Kirtipur; First Edition 2010; ISBN: 9789937825979; Pages: 140+16; Price: NRs. 125/-.